Pengaruh Kebijakan Dividen, Leverage, Profitabilitas dan Likuiditas Terhadap Nilai Perusahaan - Wilyani Handali; Kurniawan Kurniawan; Suharto Mulyanta (Universitas Matana, 2021)
The purpose of this reseacrh was to determine the effect of dividend distribution policies that use Dividend Payout Ratio (DPR), leverage used using Debt to Equity Ratio (DER), profitability needed by using Return On Assets (ROA) and Return on Equity (ROE) and measured liquidity by using the Current Ratio hampered the value of the company collected using price to book value (PBV) in mining sector companies listed on the Indonesia Stock Exchange (IDX) in 2014-2017.This type of research is causal research. The population in this research are mining companies listed on the Indonesia Stock Exchange (IDX) in 2014-2017. The sampling technique uses purposive sampling technique. From the participation obtained by 41 sectoral companies obtained samples obtained from 10 sectoral companies listed on the Indonesia Stock Exchange (IDX) in 2014-2017, so that the research data developed must be examined 40 observations. Data analysis techniques using multiple linear regression. Based on the results of this research indicate that the dividend policy does not affect the value of the company. Leverage has a negative and significant effect on firm value. Profitability with the proxy return on assets (ROA) does not affect the value of the company. Profitability with the proxy of return on equity (ROE) does not affect the value of the company. Liquidity does not affect the value of the company.